Employing second‐order mutation for isolating first‐order equivalent mutants. (21st April 2014) - Kintis, Marinos; Papadakis, Mike; Malevris, Nicos
Summary: The equivalent mutant problem is a major hindrance to mutation testing. Being undecidable in general, it is only susceptible to partial solutions. In this paper, mutant classification is utilised for isolating likely to be first‐order equivalent mutants. A new classification technique, Isolating Equivalent Mutants (I‐EQM), is introduced and empirically investigated. The proposed approach employs a dynamic execution scheme that integrates the impact on the program execution of first‐order mutants with the impact on the output of second‐order mutants. An experimental study, conducted using two independently created sets of manually classified mutants selected from real‐world programs revalidates previously published results and provides evidence for the effectiveness of the proposed technique. Overall, the study shows that I‐EQM substantially improves previous methods by retrieving a considerably higher number of killable mutants, thus, amplifying the quality of the testing process. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This paper presents a new technique to tackle the equivalent mutant problem. The salient feature of this approach is the employment of higher‐order mutation in the classification process. More precisely, the classification scheme utilises code coverage information and second‐order mutation to classify a given set of first‐order mutants as possibly killable or possibly equivalent ones. The results suggest that the proposed method outperforms its predecessors with respect to the recall metric, without significant loss of classification precision. Copyright © 2014 John Wiley & Sons, Ltd.